Surgical management of diaphyseal fracture of femur with closed intramedullary interlocking nail - Kumar, B. S. Vijaya (International Journal of Research in Orthopaedics, 2019)
Background: A femoral fracture is a bone fracture that involves the femur. They are typically sustained in high-impact trauma, such as car crashes, due to the large amount of force needed to break the bone. The objective of the study was to evaluate the functional outcome of fractures of the shaft of the femur treated with closed intra-medullary interlocking nailing. Methods: The present study was carried out between June 2015 to May 2016 in Orthopedic Department, Vydehi institute of medical sciences and research centre, Bengaluru. Antegrade nailing using the standard intramedullary interlocking nail was performed on 50 cases who presented with shaft fractures of the femur. Results: In the present study maximum number of patients belongs to 18 to 27 years age group (24 cases) followed by 28 to 37 years age group (12 cases), maximum number of patients sustained femur fracture due to RTA (42 cases) followed by fall (08 cases), maximum number of patients sustained closed/simple femur fracture (40 cases), followed by open / compound tibia fracture (10 cases), 32 patients had excellent functional results and 10 patients had good functional outcome, while only 5 patients had fair functional outcome. Conclusions: A femur fracture is always considered a medical emergency requiring immediate evaluation and treatment in a hospital. The treatment is largely dependent on the location of the fracture and the pattern and extent of the break.